PENGARUH LIKUIDITAS TERHADAP KUALITAS LABA PADA PERUSAHAAN KONSUMEN NON-PRIMER DI BEI - Putra, Fransiscus Febryan Awiredjo; Trisnawati, Estralita (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This study aims to obtain empirical evidence of the influence of earnings persistence, liquidity and earnings power on earnings quality in non-primary consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) during 2019-2021. The sample used was selected using a purposive sampling method of 84 companies. The results of this study indicate that earnings persistence has no effect on earnings quality, liquidity has a positive effect on earnings quality and earnings power has no effect on earnings quality.